An extended approach for recovering BPMN and WebML models from legacy Web applications - Bouchiha, Djelloul; Malki, Mimoun; El Bouhissi, Houda (INFOCOMP Journal of Computer Science, 2009)
A Web application is a software system which provides its functionalities through the Web. Understanding, maintaining and re-engineering legacy Web applications requires a reverse-engineering process. In a previous work, an ontology based Web application reverse-engineering approach has been proposed for recovering data models presenting static aspect of the Web application. In this paper we extend this approach to cover not only static aspect but also the dynamic one. For this end, we recover also business process and WebML hypertext models beside the data model from the Web applications code. The main purpose of our work is to prepare legacy Web applications for a future reengineering toward semantic Web services.